Fast and Distortion-Free Short-Circuit Detection and Protection Scheme with Fault Ride-Through Capability Applied to Four-Leg VSI - Oggier, Germán Elías (2023)
The three-phase four-leg (3P4L) voltage source inverter (VSI) with LC output filter is a suitable transformerless topology to feed non-linear and unbalanced loads in four-wire applications. Both symmetrical and asymmetrical short circuits can occur on the load side. Moreover, due to the lowthermal inertia of semiconductors, fast short-circuit protections are necessary to avoid damage by overheating. This paper proposes a fast method to detect and protect a two-level 3P4LVSI, identifying the faulted phases and switching the control to a distortion-free current mode. In contrast, the healthy phases are not affected and maintain a regular operation using voltage modecontrol. The proposal is based on the instantaneous trajectory of the output voltage vector in the 3D αβ0 reference frame, which is faster than detection methods based on the RMS phase voltageand/or inductor current variation. The proposal is validated through simulation and experimental results using a 1.2 kVA 3P4L-VSI prototype under different short-circuit scenarios.